Electronic and mechanical response of graphene on BaTiO3 at martensitic phase transitions. (1st February 2018) - Verhagen, Tim; Vales, Vaclav; Kalbac, Martin; Vejpravova, Jana
Abstract: Graphene is extremely sensitive to optical, electrical and mechanical stimuli, which cause a significant variation of the band structure, thus the physiochemical properties. In our work, we report on changes of strain and doping in graphene grown by chemical vapor deposition on copper and transferred onto a BaTiO3 (1 0 0) (BTO) single-crystal. The BTO is known as a ferroelectric material, which undergoes several thermoelastic martensitic phase transitions when it is cooled from 300 K to 10 K. In order to enhance the very weak Raman signal of the graphene monolayer (ML) on the BTO, a 15 nm thin gold layer was deposited on top of the graphene ML to benefit from the surface enhanced Raman scattering. Using temperature dependent Raman spectral mapping, the principal Raman modes (D, G and 2D) of the graphene ML were followed in situ . From a careful analysis of these Raman modes, we conclude that the induced strain and doping of the graphene ML follows the martensitic phase transitions of the BTO crystal. Our study suggests potential exploitation of the graphene as a highly sensitive opto-mechanical sensor or transducer.